PENGARUH SISTEM INFORMASI AKUNTANSI, AUDIT INTERNAL, DAN PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD (Studi Kasus Pada Usaha Retail di Kabupaten Sleman Daerah Istimewa Yogyakarta) - Suci Maharetno, Andina; Dewi Astuti, Tutut (JURNAL ILMIAH EDUNOMIKA, 2025)
The purpose of this study is to test and evaluate the impact of fraud prevention on retail employees in Sleman Regency, Yogyakarta Special Region, as well as the influence of accounting information systems, internal audits, and internal controls. This type of research is known as explanatory research. A total of 35 of 40 retail employees in Sleman district, Yogyakarta Special Region, have returned the questionnaire, thus becoming the research population. A Likert scale questionnaire that complies with factor analysis and Cronbach's Alpha reliability and validity standards is a tool used to facilitate analyzing data consistency. The following conclusions are drawn from the data analysis: (1) The findings of the first hypothesis test indicate no effect on Fraud Prevention in retail businesses in Sleman Regency, Yogyakarta Special Region. (2) The findings of the second hypothesis test indicate no effect on Fraud Prevention in retail businesses in Sleman Regency, Yogyakarta Special Region. (3) The findings of the third hypothesis test do not affect Fraud Prevention in retail businesses in Sleman Regency, Yogyakarta Special Region. Keywords: accounting information systems, internal audit, internal control, and fraud prevention